The Implementation Gap of Urban Green Space Policy: A Mixed-Methods Analysis of Political Will and Spatial Inequity in Indonesia’s Decentralized Governance - Ulfah Nur Hakimah; Oti Kusumaningsih; Anggara Setya Saputra (HM Publisher, 2025)
Rapid urbanization in emerging economies frequently outpaces environmental planning, creating severe ecological deficits. In Indonesia, Law Number 26 of 2007 mandates that local governments maintain at least 30% of their urban area as green open space (RTH). However, compliance remains critically low in secondary cities. This study employs a Sequential Explanatory Mixed-Methods design to evaluate the implementation gap in Banyumas Regency, Indonesia. Utilizing longitudinal policy data from 2019 to 2023, a stratified random survey of 300 residents, Geographic Information System (GIS) analysis, and Structural Equation Modeling (SEM), this research quantifies the divergence between statutory targets and spatial reality. Results indicate a critical implementation gap, with Public RTH covering only 2.23% of the urban area, far below the 20% public target. While the total RTH area increased by 11.05% over five years, the growth rate is insufficient. Spatial analysis reveals a Gini coefficient of 0.65, highlighting severe inequality where green space is concentrated in administrative cores while peri-urban districts remain green deserts. Structural Equation Modeling confirms that Political Will (beta = 0.62) significantly influences implementation success, while Resource Constraints (beta = -0.48) act as a critical inhibitor. Qualitative analysis identifies a resource trap, where decentralized governance incentivizes revenue-generating infrastructure over environmental assets. The study concludes that achieving the 30% target requires a paradigm shift from state-centric planning to collaborative governance and the establishment of a municipal Land Banking Agency.